2000
DOI: 10.1177/096120330000900104
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal pseudo-obstruction in systemic lupus erythematosus: an uncommon but important clinical manifestation

Abstract: IpsO is an uncommon but important manifestation of SLE. The underlying pathology is not fully understood but it may be related to immune complex deposition. The finding of coexisting ureterohydronephrosis suggests that there may also be a central smooth muscle motility problem of neuropathic or myogenic pathophysiology which may or may not be secondary to vasculitis. Early recognition and treatment of IpsO in SLE is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
114
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 12 publications
9
114
0
6
Order By: Relevance
“…These findings argue for the existence of a systemic circulating factor causing smooth muscle injury by a mechanism other than vasculitis (although the histopathologic basis for concomitant hydronephrosis and megacholedochus are yet to be determined). A good clinical response to immunosuppressive treatment has led some to hypothesize that the intestinal myopathy may be a direct result of an autoimmune phenomenon in the bowel wall [5] , and a common autoantibody against smooth muscle cells has been proposed [4] . It has been shown that autoantibodies against proliferating cell nuclear antigen (PCNA) have been detected exclusively in SLE patients and 2 cases were presented in which patients with this antibody in systemic sclerosis developed CIPO [7] ; whether PCNA autoantibodies play a role in GML, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings argue for the existence of a systemic circulating factor causing smooth muscle injury by a mechanism other than vasculitis (although the histopathologic basis for concomitant hydronephrosis and megacholedochus are yet to be determined). A good clinical response to immunosuppressive treatment has led some to hypothesize that the intestinal myopathy may be a direct result of an autoimmune phenomenon in the bowel wall [5] , and a common autoantibody against smooth muscle cells has been proposed [4] . It has been shown that autoantibodies against proliferating cell nuclear antigen (PCNA) have been detected exclusively in SLE patients and 2 cases were presented in which patients with this antibody in systemic sclerosis developed CIPO [7] ; whether PCNA autoantibodies play a role in GML, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the anecdotal reports of patients with apparent GML in an attempt to further our understanding of the pathophysiolog y of this phenomenon. An over view of the pathological analysis of the gastrointestinal tract in lupus patients with CIPO revealed the following characteristics: widespread myocyte necrosis in the muscularis propria with active inflammatory cell infiltrate [5] , severe atrophy and fibrosis of the muscularis [3,5] , active serositis with serosal thickening and fibrosis [5] , little or no evidence of vasculitis or injury to bowel innervation [3][4][5] , and absence of thromboembolic disease [4,5] . It is notable that intestinal myonecrosis is observed without significant lupus vasculitis, often involving smooth muscle dysfunction in another organ system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological mechanisms underlying the development of IPO in SLE have not been clearly elucidated, although proposed mechanisms include development of visceral smooth muscle injury and dysmotility subsequent to immune-complex mediated vasculitis. The smooth muscle dysfunction may be diffuse and may involve urinary and biliary systems as well [8][9][10]. Mesenteric ischemia due to LMV may be associated with a number of findings in abdominal CT including focal or diffuse intestinal wall thickening, enlarged intestinal segments, abnormal contrast enhancement in the intestines (target or double halo sign), mesenteric edema, engorgement of the vascular structures penetrating the intestinal wall, and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intestinal pseudo-obstruction (CIP) is characterized by ineffective intestinal propulsion without any mechanical obstruction of the gut (9). Symptoms of CIP include abdominal pain and distension, nausea and vomiting, constipation and weight loss.…”
Section: Discussionmentioning
confidence: 99%